Move the couch where? : Developing an augmented reality multimodal interface - Irawati, S.; Green, S.; Billinghurst, M.; Duenser, A.; Ko, H. (Proceedings - ISMAR 2006: Fifth IEEE and ACM International Symposium on Mixed and Augmented Reality, 2006)
This paper describes an augmented reality (AR) multimodal interface that uses speech and paddle gestures for interaction. The application allows users to intuitively arrange virtual furniture in a virtual room using a combination of speech and gestures from a real paddle. Unlike other multimodal AR applications, the multimodal fusion is based on the combination of time-based and semantic techniques to disambiguate a users speech and gesture input. We describe our AR multimodal interface architecture and discuss how the multimodal inputs are semantically integrated into a single interpretation by considering the input time stamps, the object properties, and the user context. ？2006 IEEE.